Implementasi prinsip kedaulatan rakyat dalam sistem ketatanegaraan indonesia - Rohmah, Norul (Maliki Interdisciplinary Journal, 2025)
The principle of popular sovereignty is a fundamental foundation in Indonesia’s constitutional system, reflected in various aspects of state administration. This study aims to examine how this principle is implemented within the structure and mechanisms of Indonesia’s constitutional system post-reformation. Using a qualitative descriptive method through literature review of legislation, official state documents, and academic sources, it was found that popular sovereignty is implemented through democratic general elections, a representative system in legislative institutions, and active public participation in policy-making processes. However, in practice, there are still several challenges such as low political participation, dominance of political elites, and weak accountability of state institutions. Therefore, strengthening political education, transparency, and institutional reform are necessary to ensure that the principle of popular sovereignty is truly realized in the life of the nation and state.